Positivity rates and subsequent patient dispositions after utilisation of cervical spine imaging referral guidelines in Singapore - Yi Xiang Tay; Shane J. Foley; Ronan Killeen; Marcus E. H. Ong; Robert Chun Chen; Lai Peng Chan; Eu Jin Tan; May San Mak; Wenlu Hou; Jonathan P. McNulty (Insights into Imaging)
Abstract Objectives This study seeks to evaluate the imaging characteristics and patient outcomes from the imaging recommendations of the ACR Appropriateness Criteria (AC), the ESR iGuide, and RCR iRefer. Materials and methods This retrospective study evaluated cervical spine X-rays and CTs performed consecutively in a Singapore emergency department (ED) between October 1st and December 31st, 2022. Patient demographics, clinical diagnosis, ED clinical notes, and radiological findings were extracted from the electronic health record and subsequently reviewed to determine the associated imaging recommendations. Results 452 (mean age, 56 ± 17.3 years, 54.9% female) and 153 (mean age, 52.8 ± 21.4 years, 65.4% male) patients underwent X-ray and CT cervical spine, respectively. According to ACR AC and ESR iGuide, the positivity rate (4.3–7.2%) was the highest for appropriate studies and the lowest (0%) for inappropriate studies. For RCR iRefer, positivity rates (1.1–7.0%) were only observed for imaging classified as “Indicated only in specific circumstances”. There was a minimal difference in the proportion of patients with radiological findings that were categorised as positive and negative across the recommendations from the three guidelines. Most patients with inappropriate imaging in the X-ray cohort were discharged home or referred to specialists, whereas those in the CT cohort were primarily admitted to the hospital for conditions unrelated to the cervical spine. Conclusions Inappropriate cervical spine imaging was associated with a lack of positive, significant findings. Imaging referral guidelines are specific and can effectively rule out significant pathology when imaging in the ED is not indicated. Clinical practice in the ED must incorporate imaging referral guidelines. Critical relevance statement Imaging referral guidelines were effective in excluding a positive finding in traumatic and non-traumatic patients, especially when aligned with evidence-based clinical criteria. Key Points There are numerous imaging referral guidelines with unique methodologies, but the impact of individual imaging recommendations on imaging characteristics and patient dispositions remains unclear. There is minimal difference in the positivity rates across individual imaging recommendations from all three imaging referral guidelines. Inappropriate cervical spine imaging was associated with a lack of positive, significant findings. Guidelines are still effective in excluding significant pathology when imaging is not indicated Graphical Abstract